Secretion of hormones of hypophysis, sexual gland and adrenals in patients with postoperative cicatricial-commissural epiduritis - L. V. Rodionova; Z. V. Koshkareva; V. A. Sorokovikov; O. V. Sklyarenko; A. V. Gorbunov (Acta Biomedica Scientifica, 2013)
The article is devoted, to the study of secretion of hormones of hypophysis, sexual gland and adrenals in patients with postoperative cicatricial-commissural epiduritis. Concentration of some hormones of hypophysis, sexual glands and adrenals in blood serum of 45 patients with postoperative cicatricial-commissural epiduritis before and. after standard conservative treatment was defined. Typical changes in secretion of studied hormones at postoperative cicatricial-commissural epiduritis were revealed. It was showed that standard scheme of treatment partly grades revealed endocrine disorders. Appropriateness of including research of hormonal profile for solving the problem of its possible correction in the complex of examination of patients with postoperative cicatricial-commissural epiduritis and. of calling endocrinologist for the examination of patients and further enhancement of the scheme of their treatment was proved.